Analisis Eksplorasi Data Masa Rawat Kelahiran Bayi Menggunakan Pendekatan Pohon Regresi (An Exploratory Analysis of Birth Nursing Home Data Using Regression Tree Approach) - Abdul Kudus; Aunuddin Aunuddin; Aji Hamim Wigena; Bunawan Sunarlim (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2001)
The main objective of this study is to explore birth nursing home data using treestructuredregression. A nonparametrica pproacho f tree-structuredr egressionmethod is implementedin to this data. This approachi s slightly differentf i'omwidely used CART methodologyo f Breiman et al. (19E4,C lassificationa ndRegressioTn rees,C hapmana nd Hall, New York). Thed ffirencesb etweenth emare thosei n splilting rules and pruning strategy.C onventionasl plitting rules arereplacedh y rules basedo n log-rank statisticsfo r two sarnplcd ata. Whereasn ewpruning strategiesa re also devised.F inal resulto f thiss tudyi s to developg roupsaf babiesb asedo n covariates. This studyr evealst hat birth wcighl existenceo fphysiologicaml alfunctiond uring nursingh omea nd levelo f cducationo f molherdetermineg roups development,